Sonnets of Catharina von Greiffenberg Methods of Composition - Kimmich, Flora (UNC Studies in the Germanic Languages and Literatures, 1975)
This study presents interpretation and criticism of Catharina von Greiffenberg's "Geistliche Sonnette" (1662) with contrastive discussions of the process and structure of Gryphius' sonnets. The author uses an eclectic method to explore the sonnets as viable poetic constructs. She arrives at new conclusions on the nature of the two poets' gifts and on the peculiarities and possibilities of the sonnet as a short lyric form.